Schallabstrahlung von überströmten ebenen Ein- und Mehrplattensystemen in Kavitäten - Osterziel, Johannes; Krömer, Florian; Winter, Philipp; Lerch, Reinhard (Fortschritte der Akustik - DAGA, 2018)

Sound Radiation of Aerodynamically Excited Flat Plates into Cavities - Osterziel, Johannes; Zenger, Florian; Becker, Stefan (Applied Sciences, 2017)
Flow-induced vibrations and the sound radiation of flexible plate structures of different thickness mounted in a rigid plate are experimentally investigated. Therefore, flow properties and turbulent boundary layer parameters are determined through measurements with a hot-wire anemometer in an aeroacoustic wind tunnel. Furthermore, the excitation of the vibrating plate is examined by laser scanning vibrometry. To describe the sound radiation and the sound transmission of the flexible aluminium plates into cavities, a cuboid-shaped room with adjustable volume and 34 flush-mounted microphones is installed at the non flow-excited side of the aluminium plates. Results showed that the sound field inside the cavity is on the one hand dependent on the flow parameters and the plate thickness and on the other hand on the cavity volume which indirectly influences the level and the distribution of the sound pressure behind the flexible plate through different excited modes.
Keywords: aeroacoustics; flow-excited; vibration; sound radiation; acoustic coupling; turbulent; boundary layer